Transport of short-lived halocarbons to the stratosphere over the Pacific Ocean - Filus, Michal T.; Atlas, Elliot L.; Navarro, Maria A.; Meneguz, Elena; Thomson, David; Ashfold, Matthew J.; Carpenter, Lucy J.; Andrews, Stephen J.; Harris, Neil (European Geosciences Union, 2020)
The effectiveness of transport of short-lived halocarbons to the upper troposphere and lower stratosphere remains an important uncertainty in quantifying the supply of ozone-depleting substances to the stratosphere. In early 2014, a major field campaign in Guam in the western Pacific, involving UK and US research aircraft, sampled the tropical troposphere and lower stratosphere. The resulting measurements of CH3I, CHBr3 and CH2Br2 are compared here with calculations from a Lagrangian model. This methodology benefits from an updated convection scheme that improves simulation of the effect of deep convective motions on particle distribution within the tropical troposphere. We find that the observed CH3I, CHBr3 and CH2Br2 mixing ratios in the tropical tropopause layer (TTL) are consistent with those in the boundary layer when the new convection scheme is used to account for convective transport. More specifically, comparisons between modelled estimates and observations of short-lived CH3I indicate that the updated convection scheme is realistic up to the lower TTL but is less good at reproducing the small number of extreme convective events in the upper TTL. This study consolidates our understanding of the transport of short-lived halocarbons to the upper troposphere and lower stratosphere by using improved model calculations to confirm consistency between observations in the boundary layer, observations in the TTL and atmospheric transport processes. Our results support recent estimates of the contribution of short-lived bromocarbons to the stratospheric bromine budget.